Political knowledge at work: Conceptualization, measurement, and applications to follower proactivity. Issue 2 (15th September 2019) - Granger, Steve; Neville, Lukas; Turner, Nick
Abstract : In this paper, we conceptualize and integrate a measure of political knowledge into the broader literatures on political behaviour, proactivity, and followership. Political knowledge refers to an individual's perceived understanding of the relationships, demands, resources, and preferences of an influential target, such as their leader. We examine political knowledge in the follower–leader context with two studies of employees ( N s = 301 & 492) and two studies of follower–leader pairs ( N s = 187 & 130 dyads). Findings generally support the convergent and discriminant validity of our political knowledge measure. In addition, we find consistent evidence for the mediating role of political knowledge of one's leader in the relationship between follower political skill and political will with self‐reported follower proactive behaviours. Taken together, the results contribute to the political influence framework and offer insight into the importance of 'knowing your leader' in enabling followers to engage in politically risky proactivity. Practitioner points: Political knowledge describes an individual's understanding of specific influential others' relationships, demands, resources, and preferences. Followers with political knowledge are more likely to take charge and enact change, which we think is because this knowledge makes enacting change seem less risky. Leaders seeking to improve their followers' political knowledge should focus on building high‐quality relationships with followers; these relationships are positively associated with political knowledge.